Phytometers and light distribution in rubber tree canopy - Castro, P.R.C.; Barbosa, L.M.; Nastri, V.D.F.; Angelocci, L.R. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1990)
Phytometers were used as standard systems to verify the effect of vertical distribution of leaf area in the canopy profile of Hevea brasiliensis Muell. Arg. cv. RRIM 600 under Rio Claro (SP) conditions and the relation of leaf dispersion to the penetration of light and photosynthesis. These ecological indicators were installed in 30 uniform and randomized trees, with 60 phytometers distributed at 1.50, 1.20 and 3.00 meters above the soil. Variations in growth analysis parameters of the indicator plant (Beta vulgaris L. cv. Asgrow Wonder) were established in three 14 days periods in May, July and September. As from these data, LAR and SLA showed higher values in the upper canopy, while DMV, LAV, RGR, NAR and LWR presented lower values in the lower canopy. Light distribution varied with the hour of the day. The coefficient of absorption of the incoming solar radiation increased in the morning period, presenting a tendency to attain the best landing-place of the asymptot near 11:00 AM and extending throughout the afternoon. The average of the coefficient of absorption at the landing-place of the asymptot was 0.588 for rubber tree.